MODEL REGRESI LINIER DENGAN METODE BACKWARD DAN FORWARD - M. S. Noya Van Delsen; H. W. M. Patty; N. Lalurmele (VARIANCE: Journal of Statistics and Its Applications, 2019)
Obligations are undertaken by the community before claiming their rights as citizens one of them is by paying taxes. Local tax is a compulsory fee imposed by the local government that is forced and used as much as possible to run the government. In determining the regression model, the factors involved by local taxes are Gross Regional Domestic Product (GRDP), Inflation and Population. The discussion in this research is about the comparison of a backward and forward method on multiple linear regression, and make a model with the program expected to be used to model the regression model on local taxes appropriately. Comparison of a regression model based on the GRDP in Ambon method backward and forward processed with the help of SPSS produce a model of the same, that is . The regression model generated by the method backward and forward involves only one variable (GRDP) with the value of R2 the same is equal to, 0,972 or 97.2%. So there is no difference between the regression model using either method backward or forward.